Peran Dan Hambatan Satuan Polisi Pamong Praja Kota Madiun Dalam Mengendalikan Peredaran Minuman Beralkohol - Krista Yitawati; Meirza Aulia Chairani; Bambang Sukarjono; Abednego Aprillino (Universitas Merdeka Madiun, 2024)
This study aims to determine the role, obstacles and efforts of the Madiun City Pamong Praja Police Unit in carrying out the enforcement of local regulations related to the circulation of alcoholic beverages. This research uses the Empirical Legal Research Method, with primary data sources from interviews and observations at the Civil Service Police Unit and one of the cafes that sells alcoholic beverages in Madiun, as well as secondary data sources, namely Regional Regulation No. 8 of 2017 concerning Control of Alcoholic Beverage Distribution and Retribution for Alcoholic Beverage Sales Location Permits. SatpolPP Madiun City plays a role in carrying out the enforcement of local regulations related to the distribution of alcoholic beverages in Madiun City by carrying out routine operations together with the Madiun City Police with the Criminal Investigation Sub-field which is approximately ten to fifteen operations every month based on the budget that has been approved by the DPRD. The obstacles faced are sourced from within the institution's own organisation or Internal and sourced from outside the organisation or External. Satpol PP Madiun City makes several efforts in various ways, including Satpol PP is required to work with what infrastructure has been provided, Satpol PP tries to carry out its work duties according to the applicable SOP, on call when suddenly required to carry out its work duties.